The Effects of Injected Testosterone Dose and Age on the Conversion of Testosterone to Estradiol and Dihydrotestosterone in Young and Older Men - Kishore M. Lakshman; Beth Kaplan; Thomas G. Travison; Shehzad Basaria; Philip E. Knapp; Atam B. Singh; Michael P. LaValley; Norman A. Mazer; Shalender Bhasin (2010)
During testosterone (T) therapy, T is partly converted to 17beta-estradiol (E2) and 5alpha-dihydrotestosterone (DHT). Effects of age, testosterone dose, and body composition on total and free E2 and DHT levels are unknown.We evaluated age and dose-related differences in E2 and DHT levels in response to graded doses of testosterone enanthate in young and older men.Fifty-one young (aged 19-35 yr) and 52 older (aged 59-75 yr) men completed treatment with monthly injections of a GnRH agonist plus randomly assigned weekly doses of testosterone enanthate (25, 50, 125, 300, or 600 mg) for 5 months.During testosterone administration, total and free E2 levels increased dose-dependently (dose effect, P<0.001) in both young and older men. Total and free E2 levels and E2:T ratios during T administration were higher in older than young men, but age-related differences in free E2 and free E2:T ratios were not significant after adjusting for testosterone levels, percentage fat mass, and SHBG. DHT levels and DHT:T ratios were dose-related but did not differ between young and older men. Mechanistic modeling of free hormone data revealed that the conversions of T to E2 and DHT were both consistent with saturable Michaelis-Menten kinetics. The in vivo Km values were estimated to be 1.83 nm for aromatase and 3.35 nm for 5alpha-reductase, independent of age. The Vmax parameter for E2 was 40% higher in older men than younger men, but Vmax for DHT was not significantly different between age groups.During im testosterone administration, E2 and DHT levels exhibit saturable increases with dose. The rate of whole body aromatization is higher in older men, partly related to their higher percentage fat mass, SHBG, and testosterone levels.